Avaliação de fontes proteicas utilizadas na alimentação dos moradores da Comunidade São José, Rio Arapiuns - Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2015)
In the Amazon region, the occupation of lowland areas is based on multiple use strategies environments, with activities such as forest extraction, small-scale livestock, agriculture, hunting and fishing. This process results from the emphasis given by the traditional communities, inhabitants of the lowland, the predominance of survival strategies in response to changing opportunities presented in the regional economy. This study aimed to evaluate usage patterns of animal resources accessible to the St. Joseph community, located in Arapiuns river in the city of Santarém, Pará. This study analyzes 10 families, where the first phase of work in which a survey was carried along the these families, it was observed that 40% of families are fishermen, 40% are public employees and 20% are retired. Families consume fish between 3-6 days a week, with 80% of these households consuming fish use the fishery to obtain this food item. The main species consumed are: acaratinga, pacu, catfish, jaraqui, cigar, aracu, Marapa, Apapa, hake, peacock bass and puppy. In addition, game meat, and poultry breeding have a very small share of the food item as families.
Keywords: Amazônia; Fonte proteica; Rio Arapiuns; CNPQ:: CIÊNCIAS BIOLÓGICAS